2020
DOI: 10.1080/02640414.2020.1830543
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid neuromuscular training promotes musculoskeletal adaptations in inactive overweight and obese women: A training-detraining randomized controlled trial

Abstract: This study investigated the effects of a 10-month high-intensity interval-type neuromuscular training program on musculoskeletal fitness in overweight and obese women. Forty-nine inactive females (36.4±4.4 yrs) were randomly assigned to either a control (N=21), a training (N=14, 10 months) or a training-detraining group (N=14, 5 months training followed by 5 months detraining). Training used progressive loaded fundamental movement patterns with prescribed work-to-rest intervals (1:2, 1:1, 2:1) in a circuit fas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(42 citation statements)
references
References 42 publications
4
38
0
Order By: Relevance
“…In contrast, there is evidence that it is not clear if HIIT can be a feasible and enjoyable exercise approach for the masses as an additional public health policy supporting the benefits of long-term exercise using such an aggressive training modality [27,28]. Additionally, recent research shows that circuit-type exercise programs incorporating HIIT, functional fitness and bodyweight training into a small-group gym getting elicit favorable changes in several physiological [29,30] and psychological [31] indicators of previously inactive, middle-aged women with overweight or obesity. On the other side, large multipurpose facilities are still popular in Greece and may be this fact supports the finding that traditional exercise modes such as strength training with free weights (#9) and group training (#12) are considered attractive at both national and international level [15].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, there is evidence that it is not clear if HIIT can be a feasible and enjoyable exercise approach for the masses as an additional public health policy supporting the benefits of long-term exercise using such an aggressive training modality [27,28]. Additionally, recent research shows that circuit-type exercise programs incorporating HIIT, functional fitness and bodyweight training into a small-group gym getting elicit favorable changes in several physiological [29,30] and psychological [31] indicators of previously inactive, middle-aged women with overweight or obesity. On the other side, large multipurpose facilities are still popular in Greece and may be this fact supports the finding that traditional exercise modes such as strength training with free weights (#9) and group training (#12) are considered attractive at both national and international level [15].…”
Section: Discussionmentioning
confidence: 99%
“…The 20 papers within this review examined 619 participants with mean age ranging from 18 to 63 (Additional file 2 : Table S2). Three studies from the same authors observed the same group of participants [ 18 , 39 , 40 ]. Another two studies of the same group of authors reported on findings from the same subjects [ 32 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…One study examined the effects of assignment to intervention for the intention to treat [ 25 ], and the remaining studies examined the effects of adherence to the intervention. Three studies from the same group of authors demonstrated random sequence generation and adequate allocation concealment [ 18 , 39 , 40 ]. Another two studies demonstrated random sequence generation without adequate allocation concealment [ 25 , 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…Briefly, the training regimen was a hybrid of both aerobic-and resistance-based exercises of low volume (<30 min/session; 3 days/week) and incorporated low-to moderate-impact cardiovascular drills and compound RT exercises into an intermittent manner. Such an intermittent-based, multicomponent exercise mode in which both the cardiovascular and musculoskeletal systems are engaged simultaneously, at various intensities, throughout a single session cannot be classified as either MICT, or HIIT or RT [23][24][25]. Participants were encouraged to perform as many repetitions as possible for each exercise aiming to maintain the exercise intensity at levels higher than 75% of maximal heart rate (MHR).…”
Section: Exercise Training Programmentioning
confidence: 99%
“…Recent studies, however, revealed that HIIT-like protocols incorporating multiplanar, neuromuscular exercises performed in a circuit fashion, also called hybrid training protocols, may induce not only weight and fat loss, but they can also improve body composition, cardiorespiratory (CRF) and musculoskeletal fitness as well as several psychological health indicators related to exercise using only ~100 min/week [23][24][25]. Hybrid-type training is a new multicomponent exercise mode activating simultaneously both the cardiovascular and the musculoskeletal system throughout the same exercise session, at various intensities, using both muscle-strengthening exercises and dynamic cardiovascular activities [23].…”
Section: Introductionmentioning
confidence: 99%